1975
DOI: 10.1677/joe.0.0670317
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Activity in Kidney, Adrenal and Gonadal Tissue of Rats Treated Neonatally With Androgen or Oestrogen

Abstract: A single injection of 300 mug oestradiol benzoate (OEB) or 1.25 mg testosterone propionate (TP) on day 1 of life led to significant changes in the activity of enzymes involved in steroid hormone metabolism in kidney, adrenal and gonadal tissues of adult rats. In the kidney, the enzyme activities of male rats reacted to OEB, but not TP, by the development of normal female levels. With one exception the enzyme activities of the kidney of female rats did not respond to either steroid. In the adrenal of both sexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1977
1977
1990
1990

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…However, the response of polycystic ovaries in androgen-sterilized rats to acute LH injections, in terms of the secretion of these two metabolites, remained small in spite of an increase in progesterone secretion (groups 2 vs 4). This indicates that 5a-reductase activity in follicular polycystic ovaries was lower than that in normal pre¬ ovulatory ovaries, as has been observed in vitro by Ghraf, Hoff & Schriefers (1975).…”
Section: Discussionsupporting
confidence: 53%
“…However, the response of polycystic ovaries in androgen-sterilized rats to acute LH injections, in terms of the secretion of these two metabolites, remained small in spite of an increase in progesterone secretion (groups 2 vs 4). This indicates that 5a-reductase activity in follicular polycystic ovaries was lower than that in normal pre¬ ovulatory ovaries, as has been observed in vitro by Ghraf, Hoff & Schriefers (1975).…”
Section: Discussionsupporting
confidence: 53%
“…This indicates that the 5a-reductase activity in polycystic ovaries is lower than in ovaries with normal follicles, as has been observed in vitro by Ghraf et al (1975). The secretion of 5ct-pregnane-3,20-dione and 3a-hydroxy-5cx-pregnan-20-one is significantly higher in ovaries with follicles than in those with¬ out (Sawada & Ichikawa 1978).…”
Section: Discussionmentioning
confidence: 70%
“…Glira/ e t al. [9] observed that neo natal androgenization had no effect on adult adrenal 5a-reductase, whereas estrogenization caused an increase in the enzyme. In contradistinction to these results, Goldman et al [10] reported a lowering of 5a-reductase by neonatal androgenization.…”
Section: Discussionmentioning
confidence: 97%